Comparison of lower limb biomechanics during single leg landing between male and female volleyball recreational athletes - Fadzir, Amir Arifudeen Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Previous study has shown that frontal plane knee joint kinematic (i.e., abduction or adduction) were significantly higher in female than male. The purpose of this study was to compare the lower extremities (i.e., Ankle, Hip and Knee joint) kinetics (i.e., moments) and kinematics (i.e., angles) variables between male (n=12) and female (n=15) recreational volleyball athletes from Universiti Sains Malaysia, Health Campus. Kinetic and kinematic variables of the athletes were measured and identified at two phases of landing (i.e., Initial Contact and Maximum vGRF) using Qualisys Track Manager (v2.16) which consisted of six motion capture camera and one Bertec force platform. Then inverse dynamic calculation for musculoskeletal model was conducted using V3D Pro software (v5). All the test trials were conducted at Exercise and Sports Science Laboratory, School of Health Science, USM. Athletes were instructed to do Single Leg Landing (SLL) from Counter Movement Jump (CMJ) for a total of three trials on the force plate. Result of this study showed, there were no significant differences on all kinematics variables at both phases of Initial Contact (p = 0.481, 0.635, 0.394) and MvGRF (p = 0.679, 0.978, 0.964). Similar no significant result was also shown on kinetic variables at both Initial Contact (p = 0.710, 0.774, 0.871) and MvGRF (p = 0.609, 0.662, 0.387) between male and female athletes although the vGRF (p = 0.032, 0.000) was proven to be significantly different. Inference of this research revealed that both gender groups shown to have normal DKV, and they implement an ergonomic posture during landing which can help to reduce risk of lower limb injuries. Result of this study can potentially help our athletes and their coaches in planning exercise and training program that focus on medial-lateral motion of lower limb in safe and effective conditions.